UPAYA PENGEMBANGAN DAN PENINGKATAN PENDAPATAN INDUSTRI KREATIF DI KOTA PALEMBANG (Universitas Muhammadiyah Palembang, 2023)
Purpose –This research aims to determine the problems still faced by the creative industry in Palembang City. To find out and formulate policies, strategies, programs and activities that must be carried out in the development of creative industries in Palembang City. To find out the efforts that must be made to encourage an increase in the income of creative industry players in Palembang City. Design/methodology –The area of this study is Palembang City. Types of data are secondary data and primary data, primary data obtained through interviews, secondary data, in the form of data and/or information obtained from documentation. The analysis technique uses SWOT analysis. Findings - The creative industry in the City of Palembang has contributed to the progress and development of the economy in the City of Palembang in particular and in South Sumatra in general, creative industry businesses in the City of Palembang are still possible to develop, so that they still provide promising business opportunities in the future, business The creative industry in Palembang City is still faced with HR, marketing, management and capital problems. Creative industry businesses in Palembang City have absorbed a lot of labor, so that the creative industry in Palembang City has contributed to overcoming the unemployment problem.